41. THE CHARACTERISTICS OF PREMATURE RUPTURE OF MEMBRANES PREGNANCIES AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical and subclinical characteristics premature rupture of membranes at pregnancies at gestational age from 24 to 34 weeks at Hanoi Obstetrics and Gynecology Hospital. Materials and method: A retrospective cross-sectional descriptive study on 217 pregnant women with preterm rupture of membranes at gestational age from 24 weeks 0 day to 33 weeks 6 days at Hanoi Obstetrics and Gynecology Hospital from January 2022 to December 2022. Results: The average age of pregnant women was 30.1±6.1. Premature rupture of membranes is common in pregnant women with a history of previous cesarean section (33.2%), history of abortion (20.7%), and miscarriage and stillbirth (15.6%). Most women with premature rupture of membranes have normal amniotic index (64.5%) when admitted to the hospital. The number of white blood cells in the mother’s blood
Keywords: Premature rupture of membranes, clinical, paraclinical.